Genetic testing practices among specialist physicians who treat prostate cancer: A Canadian cross-sectional survey - Yip, Steven M.; Morash, Christopher; Kolinsky, Michael P.; Kapoor, Anil; Ong, Michael; Selvarajah, Shamini; Nuk, Jennifer; Compton, Katie; Pouliot, Frederic; Lavallée, Luke T.; et al. (Canadian Urological Association Journal, 2023)
INTRODUCTION: In patients with prostate cancer (PCa), the identification of an alteration in genes associated with homologous recombination repair (HRR) has implications for prognostication, optimization of therapy, and familial risk mitigation. The aim of this study was to assess the genomic testing landscape of PCa in Canada and to recommend an approach to offering germline and tumor testing for HRR-associated genes. METHODS: The Canadian Genitourinary Research Consortium (GURC) administered a cross-sectional survey to a largely academic, multidisciplinary group of investigators across 22 GURC sites between January and June 2022. RESULTS: Thirty-eight investigators from all 22 sites responded to the survey. Germline genetic testing was initiated by 34%, while 45% required a referral to a genetic specialist. Most investigators (82%) reported that both germline and tumor testing were needed, with 92% currently offering germline and 72% offering tissue testing to patients with advanced PCa. The most cited reasons for not offering testing were an access gap (50%), uncertainties around who to test and which genes to test, (33%) and interpreting results (17%). A majority reported that patients with advanced PCa (74–80%) should be tested, with few investigators testing patients with localized disease except when there is a family history of PCa (45–55%). CONCLUSIONS: Canadian physicians with academic subspecialist backgrounds in genitourinary malignancies recognize the benefits of both germline and somatic testing in PCa; however, there are challenges in accessing testing across practices and specialties. An algorithm to reduce uncertainty for providers when ordering genetic testing for patients with PCa is proposed.